Prof. Kenji Suzuki: craziness on the road to success - Fan, Wei-En (Journal of Thoracic Disease, 2018)
On October 28 and 29, 2017, the 16th Annual Meeting of Taiwan Association of Thoracic & Cardiovascular Surgery (TATCS 2017) was held in Taipei and rounded off. The grand meeting brought together numerous outstanding experts worldwide.